23.8k views
1 vote
Solve the system using elimination.

x- y = -5
3x + y = 1

A (-1, 4)
B (-3, 4)
C (-1, 2)
D (2, -2)​

User Alirabiee
by
6.2k points

1 Answer

2 votes

Answer:

A (-1, 4)

Explanation:

x- y = -5

3x + y = 1

Add the two equations together to eliminate y

x- y = -5

3x + y = 1

-------------------

4x = -4

Divide by 4

4x/4 = -4/4

x = -1

Now substitute x=-1 into the first equation

-1 -y = -5

Add 1 to each side

-1+1 -y = -5+1

-y = -4

Multiply by -1

y = 4

User HighLife
by
5.4k points